Galectin-1 is a major receptor for ganglioside GM1, a product of the growth-controlling activity of a cell surface ganglioside sialidase, on human neuroblastoma cells in culture - Kopitz, Jürgen; Reitzenstein, Carolina von; Burchert, Maria; Cantz, Michael; Gabius, Hans-Joachim (The journal of biological chemistry, 1998)
Cell density-dependent inhibition of growth and neural differentiation in the human neuroblastoma cell line SK-N-MC are associated with a ganglioside sialidase-mediated increase of GM1 and lactosylceramide at the cell surface. Because these glycolipids expose galactose residues, we have initiated the study of the potential role of galectins in such cellular events. Using specific antibodies, galectin-1 but not galectin-3 was found to be present at the cell surface. Assessment of carbohydrate-dependent binding revealed a saturable amount of ligand sites approaching 2.6 × 106 galectin-1 molecules bound/cell. Presence during cell culture of the sialidase inhibitor 2-deoxy-2,3-dehydro-N-acetylneuraminic acid or of the GM1-binding cholera toxin B subunit effected a decrease of the presentation of galectin-1 ligands by 30-50%. The assumption that GM1 is a major ligand for galectin-1 was reinforced by the correlation between the number of carbohydrate-dependent 125I-iodinated GM1-neoganglioprotein binding sites and the amount of immunoreactive surface galectin-1, the marked sensitivity of probe binding to the presence of anti-galectin-1 antibody, and the inhibition of cell adhesion to surface-immobilized GM1 by the antibody. The results open the possibility that the carbohydrate-dependent interaction between ganglioside GM1 and galectin-1 may relay sialidase-dependent alterations in this cell system.
Artikel-Version: 4. January 2021
Gesehen am 10.07.2024